Healthcare demand modelling: a systematic review - Lopes, Diana Fernandes; Santinha, Gonçalo; Ramos, Ana Luísa; Castro, Eduardo Anselmo (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
Understanding imbalances between the demand and supply of the health workforce is essential for the improvement of many health outcomes, such as equity access to healthcare services targeted by the United Nations Sustainable Development Goals in 2015. Within this context, it is crucial to have tools to support the distribution of the human health resources (HHR) considering the population needs. Many healthcare modelling exercises have been undertaken with the purpose of supporting the decision-making process. Despite the relevance of this topic, methodological weaknesses can be found in existing demand analyses. The aim of this study is to provide a systematic review of the literature surrounding healthcare demand modelling. This systematic review intends to answer the following key questions: How can healthcare demand be defined? How has healthcare demand been modelled? How to classify healthcare demand-based methods? What are the harms and barriers of modelling healthcare demand? The methodology of this systematic review was based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) statement (Moher et al., 2009).